Effect of the Inhibition of Protein Synthesis on the Establishment of Transformation by Polyoma Virus - Marin, Guglielmo (1967)
Puromycin was used to study the effect of the inhibition of protein synthesis on transformation of hamster cells (BHK21) by polyoma virus. The drug was used at a concentration (10(−4)m) which caused in these cells a drastic but fully reversible inhibition of protein synthesis. A two- to threefold enhancement of transformation rate was obtained when the cells were exposed to puromycin for a period of 5 hr that started at the end of the virus adsorption period. No further enhancement was produced by prolonging puromycin treatment up to 13 hr after infection. The possibility that the observed effect on transformation rate could be mainly attributed to cell selection by puromycin was excluded. In addition, the relevance of a number of possible secondary effects of puromycin (inhibition of cell division, inhibition of deoxyribonucleic acid synthesis, etc.) was also ruled out. The effect of puromycin on transformation appeared to be dependent on the time (relative to infection) of addition of the drug. In fact, no transformation enhancement was observed when the cells were exposed to puromycin prior to infection or beyond the 10th hr after infection. Since another drug known to affect protein synthesis (p-fluorophenylalanine) was also shown to produce similar effects, it is suggested that transformation enhancement results from the inhibition of protein synthesis during a sensitive period closely following adsorption of the virus.